Correção de erro em sistemas de comunicação quântica utilizando polarização de estados coerentes e fótons isolados - Nascimento, José Cláudio do (2006)
In this dissertation, it is realized a study of light polarization and its applications in quantum communications. Initially, the mathematical tools needed for single-photon and coherent states polarization analyses are presented: coherence matrix, Stokes parameters and polarization degree. Following, using numerical simulations, it is presented the variation of the degree of polarization of a single-photon pulse during depolarizing channel propagation. At last, the result of an experiment using coherent states, aiming to measure the degree of polarization after propagation in 200 m optical fiber is presented. The experiment is useful for determination of the parameter of the qubit depolarizing channel model. Since light polarization is easily changed when environment fluctuations are present during fiber propagation, optical schemes able to correct unpredictable polarization changes are studied. Such schemes are employed for error correction in quantum communication systems. Based on already proposed error correction schemes, two new schemes are proposed, one for systems that employs polarization of singlephoton light, and other for systems that employs polarization of two-mode coherent states, being the first active, that is, requiring a control and synchronism protocol, while the second is passive. At last, it is realized a security analysis of a quantum key distribution system, employing the proposed error correction scheme, when the same is under Fuch-Peres-Brandt attack. It is shown that using the proposed error correction scheme the presence of an eavesdropper monitoring the quantum channel is more visible.